Modulating the Electronic Structure of Single‐Atom Catalysts on 2D Nanomaterials for Enhanced Electrocatalytic Performance - Zhu, Yuanzhi; Peng, Wenchao; Li, Yang; Zhang, Guoliang; Zhang, Fengbao; Fan, Xiaobin (Small methods, 2019)
Single‐atom catalysts (SACs) on 2D nanomaterials have great potential as efficient and low‐cost electrocatalysts for clean energy technologies. The coordination environments, as well as the physicochemical properties of the 2D supports, play key roles in tuning the catalytic activity and reaction mechanism of the single‐atom centers. This review first summarizes the suitable synthetic strategies of single‐atom on different 2D supports. The methods that facilitate the formation of relative homogeneous structure and enable the regulation of the surrounding atomic environment of metal center are discussed. Furthermore, the recent progress of SACs for energy‐related electrochemical applications is reviewed, including oxygen reduction reaction, hydrogen evolution reaction, oxygen evolution reaction, CO2 reduction reaction, and nitrogen reduction reaction. The strategies about modulation of the electronic structure of single‐atom for enhanced performance are highlighted, together with a discussion of the current issues and the prospects of this field. The synthetic strategies, electronic modulation process, and energy‐related electrochemical applications of single‐atom catalysts on different 2D supports are reviewed. Works about modulation of the electronic structure for enhanced performance are highlighted. The applications involve oxygen reduction reaction (ORR), hydrogen evolution reaction (HER), oxygen evolution reaction (OER), CO2 reduction reaction (CO2RR), and nitrogen reduction reaction (NRR).